Assessing the Accountability of the Benefit Corporation: Will This New Gray Sector Organization Enhance Corporate Social Responsibility? - André, Rae (Journal of business ethics, 2012)
In recent years the benefit corporation has emerged as a new organizational form dedicated to legitimizing the pursuit of corporate social responsibility (CSR). Eschewing traditional governmental authority, the benefit corporation derives its moral legitimacy from the values of its owners and the oversight of a third party evaluator. This research identifies the benefit corporation as a new type of gray sector organization (GSO) and applies extant theory on GSOs to analyze its design. In particular, it shows how the theory of GSO accountability can be used to assess the potential of benefit corporations for enhancing CSR. This research first examines the statutes that have established benefit corporations in five states in the US, along with bills in other states, to show how legislation defines their specific public benefits and holds them accountable for delivering these benefits. It then compares the accountability of the benefit corporation with that of other corporate-centric GSOs, e.g., GSOs that closely resemble traditional corporations. It concludes with significant design-based concerns about the utility of the benefit corporation as an effective organization for implementing CSR.